Research on schools, neighborhoods, and communities toward civic responsibility - Tate, William F. (Lanham Rowman & Littlefield Publishers, Inc., 2012)
"This volume focuses on research and theoretical developments related to the role of place or geography in matters of education, human development, and health. Multiple disciplinary perspectives are presented in order to provide different views of the strengths and problems in our communities. Research presented provides historical, moral, and scientifically based arguments organized to inform understandings of civic problems as well as to present possible solutions"-Publisher.
Introduction / William F. Tate IV -- Neighborhood Inequality, Violence, and the Social Infrastructure of the American City / Robert Sampson -- Toward a Theory of Place: Social Mobility, Proximity and Proximal Capital / Odis D. Johnson, Jr. -- Urban Opportunity Structure and Racial/Ethnic Polarization / George C. Galster -- Racial Segregation in Multiethnic Schools: Adding Immigrants to the Analysis / Ingrid Gould Ellen and Katherine O'Regan with Amy Ellen Schwartz and Leanaa Stiefel -- Suburbanization and School Segregation / Sean F. Reardon, John T. Yun, and Anna K. Chmielewski -- Schools Matter: Segregation, Unequal Educational Opportunities, and the Achievement Gap in the Boston Region / John R. Logan and Dierdre Oakley -- Still Separate, Still Unequal, but Not Always So Suburban: The Changing Nature of Suburban School Districts in the New York Metropolitan Area / Amy Stewart Wells, Douglas Ready, Jacquelyn Duran, Courtney Grzesikowski, Kathryn Hill, Allison Roda, Miya Warner, and Terenda White -- Adding geospatial perspective to research on schools, communities, and neighborhoods / Mark Hogrebe -- Conceptual and Methodological Challenges to a Cultural and Ecological Framework for Studying Human Learning and Development / Carol D. Lee -- An Ecological and Activity Theoretic Approach to Studying Diasporic and Non-Dominant Communities / Kris Gutierrez and Angela E. Arzubiaga -- Reconstructing Education in America / Henry M. Levin -- Can School Improvement Reduce Racial Inequality / Stephen Raudenbush -- Seeing our way into learning science in informal environments / Shirley Brice Heath -- No Color Necessary: High School Students' Discourse on College Support Systems and College Readiness / Evellyn Elizondo, Walter R.Allen, and Miguel Ceja -- Taking Math and Science to Black Parents: Promises and Challenges of a Community-Based Intervention for Educational Change / Roslyn Arlin Mickelson, Linwood Cousins, Anne Valasco, and Brian Williams -- Research Infrastructure for Improving Urban Education / Larry V. Hedges and Nathan Jones -- Maximizing Cultural and Contextually-Sensitive Assessment Strategies in Developmental and Educational Research / Margaret Beale Spencer, Brian Tinsley, Davido Dupree, and Suzanne Fegley -- Immigrant Children Hiding in Plain Sight in the Margins of the Urban Infrastructure -- Michael A. Olivas -- Delivering High Quality Public Services to Vulnerable Families and Children in America's Cities: The Lessons from Reforming Child Welfare / Olivia Golden -- Health Disparities among African Americans in Urban Populations / Sheri Notaro -- Pandemic Preparedness: Using Geospatial Models to Inform Planning in Systems of Education and Health in Metropolitan American / William F. Tate IV -- A "Tragic Dichotomy": A Case Study of Industrial Lead Contamination and Management in a Company Town / Jill McNew -- Urban America in Distress: A Case Study Analysis of Gary, Indiana: 1968-1987 / Gail E. Wolfe -- God's Will or Government Policy: Katrina's Unveiling of History and Mass Dispersion of Black People / Jerome Morris -- The White House Office on Urban Affairs: Regionalism, Sustainability, and the Neglect of Social Infrastructure / Ronald Walters -- Epilogue -- Toward Civic Responsibility and Civic Engagement / William F. Tate, IV.
Published for the American Educational Research Association -Title page.
Includes bibliographical references and index.
Keywords: Community and school -- United States; Educational sociology -- United States; Educational equalization -- United States